2022
DOI: 10.1155/2022/7571146
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinked Decellularized Porcine Pericardium as a Substrate for Conjunctival Reconstruction

Abstract: Seeking for suitable conjunctival reconstruction substitutes to overcome the limitations of current substitutes, such as amniotic membrane, is urgent. Decellularized tissues have become a promising strategy for tissue engineering. In this study, we prepared decellularized porcine pericardium (DPP) scaffolds by the phospholipase A2 method and crosslinked them with aspartic acid (Asp) and human endothelial growth factor (hEGF) to enhance biological performance on the DPP, obtaining DPP-Asp-hEGF scaffolds. In vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Most importantly, due to the lack of posterior lamellar cellular components, these grafts barely provide a smooth epithelialized surface and restore secretory function. Although some studies have reported that implanted decellularized matrixes could support cell growth both in vitro 84 and in vivo, 85 concomitant fibrosis rather than complete reepithelization was observed on the surface of the biomaterials upon implantation in animal models 10,109 . Cellular approaches aim to restore the full function of the posterior lamella by implanting a tissue‐engineered tarsal or conjunctival equivalent into the defect area, which can be referred to as “regenerative surgery” and represents a future direction in this field.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, due to the lack of posterior lamellar cellular components, these grafts barely provide a smooth epithelialized surface and restore secretory function. Although some studies have reported that implanted decellularized matrixes could support cell growth both in vitro 84 and in vivo, 85 concomitant fibrosis rather than complete reepithelization was observed on the surface of the biomaterials upon implantation in animal models 10,109 . Cellular approaches aim to restore the full function of the posterior lamella by implanting a tissue‐engineered tarsal or conjunctival equivalent into the defect area, which can be referred to as “regenerative surgery” and represents a future direction in this field.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Ideally, bioengineered posterior lamellar substitutes should restore key structures and functions of the eyelid without additional donor‐site morbidities or postoperative complications. To date, many innovative native tissue grafts, 10 , 11 biomaterials, 12 , 13 and bioengineered tissues 14 , 15 have been proposed as posterior lamellar substitutes, some of which have been clinically used for eyelid reconstruction and have yielded promising preliminary results. 11 , 14 , 15 The bioengineering of posterior lamellar substitutes can be categorized into two distinct approaches: (1) acellular approaches, in which natural or synthetic acellular biomaterials are transplanted into defect areas to act as bioscaffolds for guiding tissue regeneration in vivo by leveraging endogenous cells and microenvironments (Figure 4a ); and (2) cellular approaches, in which bioscaffolds are precellularized in vitro to mimic specific functions of the target tissue and then transplanted to promote tissue regeneration (Figure 4b ).…”
Section: Introductionmentioning
confidence: 99%
“…E shows that the rate of cells in apoptosis in the DRCS group (9.23 ± 2.72%) is much higher than in the DRCS-Asp-hEGF (0.13 ± 0.06%). Despite these promising reports on the transplantation of acellular scaffolds for defect reconstruction [9,11], there is still scope to conduct recellularization protocols to realize clinical applications. Currently, protocols for recellularization mainly include tissue sectioning, perfusion, and direct injection [28].…”
Section: Discussionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were performed, as described previously [11]. In brief, the samples (native rabbit conjunctiva (NRC) and DRCS) were fixed using an electron microscopy fixative for 2 h at room temperature (RT) and then post-fixed with 1% OsO 4 (Ted Pella Inc., USA) for 1 h at RT after washing in PBS (pH 7.4) for 15 min thrice.…”
Section: Ultrastructural Determinationmentioning
confidence: 99%
“…In brief, pericardium grafts have been applied to correct intracardiac and diaphragm defects (Ricci et al, 2014;Yaliniz et al, 2014;Ascaso et al, 2021), as well as ischemic ventricular septal defect after acute MI (Mihalj et al, 2022). On the other hand, non-cardiac pericardium-based applications include replacement of brain dura mater (Sun et al, 2018), bleb repair, conjunctival reconstruction, cover of severe corneal wound or tendon elongation in the eye (Niegowski et al, 2020;Ashena et al, 2021;Hedergott et al, 2021;Chen et al, 2022), odontology (Solakoğlu et al, 2022) and eardrum reconstruction (de Dorldodot et al, 2013;Sainsbury et al, 2022). Furthermore it has been employed to generate a variety of bioprostheses such as vascular grafts, patches for abdominal or vaginal wall reconstruction and heart valves (Rémi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%